Hounsfield Unit for Assessing Vertebral Bone Quality and Asymmetrical Vertebral Degeneration in Degenerative Lumbar Scoliosis. Issue 22 (15th November 2020) - Wang, Hui; Zou, Da; Sun, Zhuoran; Wang, Longjie; Ding, Wenyuan; Li, Weishi
Abstract : Study Design: Retrospective analysis. Objectives: The aim of this study was to demonstrate the correlation between degenerative lumbar scoliosis (DLS) and osteoporosis based on Hounsfield unit (HU) measurement from computed tomography (CT) scans, and to investigate the asymmetrical vertebral degeneration in DLS. Summary of Background Data: The correlation between DLS and osteoporosis measured by dual-energy x-ray absorptiometry (DEXA) is debated, since T-scores measured by DEXA scan can be overestimated due to abdominal vessel wall calcification, degenerative bony spurs, and facet hypertrophy. The reliability and accuracy of HU to determine osteoporosis are shown in many reports, but it has never been used to assess the vertebral bone quality for DLS patients. Methods: Nighty-five DLS patients were retrospectively reviewed. Regions of interest for HU were measured on three coronal images of the lumbar vertebrae. HU measurement of the whole vertebrae from L1 to L5 was obtained, then HU measurement within concave and convex sides were obtained separately in L5, upper and lower end vertebrae, apex vertebrae, neutral vertebrae, stable vertebrae. Results: HU value presented a gradually increasing trend from L1 to L5. No correlation was detected between Cobb angle and mean HU value of the 5 lumbar vertebrae, or between Cobb angle and HU value of every lumbar vertebrae separately. HU value was higher within concavity than that within convexity of the same vertebrae both in major and compensatory curve. Asymmetric HU ratio in apex vertebrae positively correlated with Cobb angle. Stable vertebrae were the first proximal vertebrae that present opposite orientation of asymmetric HU ratio from the other lumbar vertebrae. Conclusion: Progression of degenerative scoliosis presents no correlation with osteoporosis based on HU measurement but could increase the asymmetrical vertebral degeneration, especially in apex vertebrae. Distraction of the pedicle screws at concave side, instead of compression of pedicle screws at convex side, should be a priority to correct lumbosacral curve. Level of Evidence: 3 Abstract : The association between osteoporosis measured by dual-energy x-ray absorptiometry and degenerative lumbar scoliosis is debated, since T-scores can be overestimated in elder patients. This is the first study to demonstrate that progression of degenerative scoliosis presents no correlation with osteoporosis based on Hounsfield unit measurement from compured tomography scans, but could increase asymmetrical vertebral degeneration.